Thrombotic thrombocytopenic purpura and ulcerative colitis – A potential link revisited - Lovy Gaur (Wolters Kluwer Medknow Publications, 2021)
Inflammatory bowel disease is known to be associated with several extraintestinal manifestations including haematological abnormalities. The association between ulcerative colitis and thrombotic thrombocytopenic purpura is largely anecdotal, described in only two case reports so far. While the existence of association remains a matter of research, what is clear is the need for prompt recognition of this complication and expedient treatment which may be life-saving. Here, we describe a patient with ulcerative colitis who developed thrombotic thrombocytopenic purpura.